Pengaruh Pembiayaan Zakat Microfinance terhadap Pengentasan Kemiskinan Material & Spiritual Mustahik di Provinsi Nusa Tenggara Barat - Nadia Nuril Ferdaus; Ahmad Zaenal Wafik; Reny Wardiningsih; Khalid Abjadi; Dewi Rispawati; Subhan Purwadinata (Jurnal Ilmiah Ekonomi Islam, 2026)
Poverty alleviation remains a top priority for institutions worldwide, as high poverty rates are often used as a key indicator of a country’s level of welfare. As one of the provinces in Indonesia, Nusa Tenggara Barat (NTB) continues to face a relatively high level of poverty. According to data from Badan Pusat Statistik (2024), the percentage of the poor population in NTB reached 12.91%. With a predominantly Muslim population (96.83%), NTB possesses Islamic social finance instruments, particularly zakat, which play an important role in poverty reduction. This study aims to analyze the role of zakat microfinance in improving the material and spiritual well-being of mustahik (zakat beneficiaries). The research employs a quantitative approach using the CIBEST data analysis method, which captures conditions before and after the intervention of productive zakat empowerment across four quadrant indices. The impact assessment of productive zakat distribution in this study serves as an evaluative analysis and is expected to provide policy recommendations for the management of Islamic social finance instruments, especially zakat, in supporting sustainable poverty alleviation.